Medidas de evaluación: performance de títulos, carteras o fondos de inversión Capacidad de selección, cantidad y calidad de títulos en una cartera - Barrera Herrera, Jorge (2009)
To study the performance and financial efficiency, which should be understood as the quality level achieved in the management on the part of managers of financial assets, measures are an absolute classic and consistency, in terms of profitability, adjusted appropriately by the total risk and systemic. There are also measures for evaluating selection and portfolio management in assessing the timing with the market. This article reviews the proposals of measures of performance of portfolio management or investment funds, beginning with the contributions of Gómez Bezares, Sharpe, Treynor, Jensen, Mazur, Henriksson, Ferruz, Sarto, Merton and Modigliani.